Seaweeds as a Fermentation Substrate: A Challenge for the Food Processing Industry - Monteiro, Pedro (2021)
Seaweeds are gaining momentum as novel and functional food and feed products. From whole consumption to small bioactive compounds, seaweeds have remarkable flexibility in their applicability, ranging from food production to fertilizers or usages in chemical industries. Regarding food production, there is an increasing interest in the development of novel foods that, at the same time, present high nutritious content and are sustainably developed. Seaweeds, because they require no arable land, no usage of fresh water, and they have high nutritious and bioactive content, can be further explored for the development of newer and functional food products. Fermentation, especially performed by lactic acid bacteria, is a method used to produce functional foods. However, fermentation of seaweed biomass remains an underdeveloped topic that nevertheless demonstrates high potential for the production of new alimentary products that hold and further improve the organoleptic and beneficial properties that these organisms are characterized for. Although further research has to be deployed in this field, the prebiotic and probiotic potential demonstrated by fermented seaweed can boost the development of new functional foods.